Medicalização em um serviço público de Saúde Mental: um estudo sobre a prescrição de psicofármacos - Ferrazza, Daniele de Andrade [UNESP]; Rocha, Luís Carlos da [UNESP]; Luzio, Cristina Amélia [UNESP] (My University, 2013)
News of the fifth version of Diagnostic and Statistical Manual of Mental Disorders (DSM-5) bringing an enlarged listing of diagnostic possibilities has fomented discussion concerning the tendency, recognizable in contemporary psychiatric practices, of including ordinary suffering of everyday life in psychiatric diagnosis and submit same to psychopharmacological treatment. The present paper brings to this discussion data obtained from field research about the prescription of psychopharmacs in the psychiatric care of a public mental health service. The results reveal that the psychiatry of the service keeps practically all of its users under prescription, and that medical discharge is extremely rare. The paper organizes elements critical to this practice and concludes that due to its inadequacy as to the objectives of promotion of personalized care concerned with autonomy and citizenship, present in the current national guidelines for public policies in mental health.

Notícias de que a quinta versão do Manual Diagnóstico e Estatístico de Transtornos Mentais (DSMV) deverá trazer uma ampliada listagem das possibilidades diagnósticas têm aquecido o debate sobre uma tendência, reconhecível em práticas psiquiátricas contemporâneas, de enquadrar em diagnósticos psiquiátricos mal-estares comuns da vida cotidiana e submetê-los a tratamento psicofarmacológico. Este artigo traz a essa discussão dados de uma pesquisa de campo sobre a prescrição de psicofármacos no atendimento psiquiátrico de um serviço público de saúde mental. Os resultados mostram que a psiquiatria do serviço mantém sob prescrição de psicofármacos praticamente todos os seus usuários e que as altas são raríssimas. O artigo organiza elementos críticos a essa prática e conclui por sua inadequação face aos objetivos de promoção de cuidados personalizados atentos à autonomia e aos preceitos de cidadania presentes nas atuais diretrizes nacionais das políticas públicas de saúde mental.
Medicalization in a mental health public service: a study on the psychotropic prescription
Keywords: Mental health; Mental health services; Medicalization; Saude mental; Serviços de saúde mental; Medicalização do social